A cyanine-based colorimetric and fluorescent probe for highly selective sensing and bioimaging of phosphate ions. (October 2016) - Liu, Bo; Wang, Huan; Yang, Dan; Tan, Rui; Zhao, Rui Rui; Xu, Rui; Zhou, Zhang Jian; Zhang, Jun Feng; Zhou, Ying
Abstract: This paper reports a near-infrared chemosensor for phosphate ions (Pi) based on Pi-controlled fluorescence off-on switching mechanism. The Pi sensor displayed colorimetric responses towards Pi with a distinct color change from green to yellow in aqueous media. Apyrase, a hydrolytic enzyme, was used to accelerate the endogenous Pi production for evaluating in vivo fluorescent sensing ability of the new cyanine based probe (1 ). In addition, the present study demonstrated potential of the newly developed chemosensor in bioimaging by performing experiments in Chinese hamster ovary (CHO) cells both in vitro and in vivo. Graphical abstract: Highlights: A near-infrared chemosensor for phosphate ions sensing is studied. The sensor displays remarkable colorimetric response towards phosphate ions. The sensor is applied in phosphate ions imaging in CHO cells in vitro and in vivo.